You Are Not Worth the Risk: Lawful Discrimination in Hiring - Scholes, Vanessa; Justus Liebig University Giessen (My University, 2014)
Increasing empirical research on productivity supports the use of statistical or `rational' discrimination in hiring. The practice is legal for features of job applicants not covered by human rights discrimination laws, such as being a smoker, residing in a particular neighbourhood or being a particular height. The practice appears largely morally innocuous under existing philosophical accounts of wrongful discrimination. This paper argues that lawful statistical discrimination treats job applicants in a way that may be considered degrading, and is likely to constrain people's freedoms in relation to employment, thus giving us reason for moral concern.
Keywords: discrimination; ethics; employment; hiring; statistical discrimination; ddc:100; ddc:330